Aplicación del sistema de costos ABC como herramienta para el proceso de toma de decisiones en la concesión de créditos de la Cooperativa de Ahorro y Crédito Indígena SAC LTDA. - Cando Chicaiza, Alba Ximena (2020)
This integrating project aimed to find a solution to the inefficient distribution of indirect costs in the microcredit process, necessary information for decision-making concerning promotion, receipt of documents, evaluation, credit verification, credit recommendations, disbursement, and follow-up; besides, it allowed to set itself a design of ABC cost system through the allocation of resources to activities, allowing to know the total cost of the granting of microcredits offered by Cooperativa de Ahorro y Crédito Indígena SAC Ltda., Machachi branch, in the period 2020. This research used a descriptive quantitative methodological approach to collect the information through bibliographic sources and by inquiring those involved in the activities described above. The proposal made a microcredit department diagnosis, elaborates on the value chain, identifies the process's activities, and cost centers hand inducers, so the indirect costs have been defined. The total cost was calculated, and the unit of granting microcredits, about the main activities. So the unit cost of the microcredit service is USD 66.12, compared to the traditional value of USD 91.99; the difference is that there are activities that only the ABC can consider at the time of calculation. They are not identified with the conventional model, dispersing the costs, because they cannot control them. This study presented a conceptual and practical model of the procedure, and the institution can apply it in different financial products once the resources, activities, drivers, and cost objects were established.